Lipase as a Chiral Selector Immobilised on Carboxylated Single-Walled Carbon Nanotubes and Encapsulated in the Organic Polymer Monolithic Capillary for Nano-High Performance Liquid Chromatography Enantioseparation of Racemic Pharmaceuticals - Ali Fouad; Frady G. Adly; Moustafa K. Soltan; Ashraf Ghanem (Molecules, 2023)
Herein, we report the preparation of lipase immobilised on single-walled carbon nanotubes (SWCNTs) as an enantioselector for capillary monolithic columns and their application in the chiral separation of racemic pharmaceuticals. The columns were prepared through the encapsulation of functionalised SWCNTs (c-SWCNTs) within an organic monolithic polymer, followed by the immobilisation of lipase over the obtained monolith, over a three-day (L1) and five-day (L2) period. The prepared columns were tested for the enantioselective nano-HPLC separation of 50 racemic drugs. A suitable resolution was achieved for 25 drugs using nano-RP-HPLC conditions for both the L1 and L2 capillaries, while no specific resolution was detected under normal-phase HPLC conditions. The developed c-SWCNT-lipase-based polymeric monolithic capillaries are a promising expansion for separating pharmaceutical enantiomers’ using nano-HPLC.